Electron transport through nanocomposite SiO₂(Si) films containing Si nanocrystals - Bratus, O.L.; Evtukh, A.A.; Steblova, O.V.; Prokopchuk, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The current transport through insulating SiO₂ films with silicon nanocrystals in Si/SiO₂(Si)/Al structures has been investigated in the wide range of temperatures (82…350 K). The nanocomposite SiO₂(Si) films containing the silicon nanoclusters embedded into insulating SiO₂ matrix have been obtained by ion-plasma sputtering of silicon target and subsequent high-temperature annealing. Based on the detailed analysis of current-voltage characteristics, calculation of some electrical parameters has been performed and the mechanism of electron conductivity of nanocomposite SiO₂(Si) films has been ascertained. The electrical conductivity of the films is based on the mechanism of hopping conductivity with variable-range hopping through the traps near the Fermi level.